2023
DOI: 10.3389/fmolb.2023.1102209
|View full text |Cite
|
Sign up to set email alerts
|

PSC-derived intestinal organoids with apical-out orientation as a tool to study nutrient uptake, drug absorption and metabolism

Abstract: Intestinal organoids recapitulate many features of the in vivo gastrointestinal tract and have revolutionized in vitro studies of intestinal function and disease. However, the restricted accessibility of the apical surface of the organoids facing the central lumen (apical-in) limits studies related to nutrient uptake and drug absorption and metabolism. Here, we demonstrate that pluripotent stem cell (PSC)-derived intestinal organoids with reversed epithelial polarity (apical-out) can successfully recapitulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The apical-in/basal-out polarity of EEO presents a challenge to study epithelial interactions with embryos or infection by microbes or viruses that reside in the uterine lumen (Boretto et al, 2019, Boretto et al, 2017, Co et al, 2019, Simintiras et al, 2021, Kakni et al, 2023, Wijesekara et al, 2023. To overcome this limitation, a suspension culture method to reverse EEO polarity was developed based on methods reported for human enteroid and airway organoids (Co et al, 2019, Co et al, 2021, Kakni et al, 2023, Wijesekara et al, 2023. Our studies demonstrate that this culture method alters the polarity of EEO without compromising their physiological hormone response and viability.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The apical-in/basal-out polarity of EEO presents a challenge to study epithelial interactions with embryos or infection by microbes or viruses that reside in the uterine lumen (Boretto et al, 2019, Boretto et al, 2017, Co et al, 2019, Simintiras et al, 2021, Kakni et al, 2023, Wijesekara et al, 2023. To overcome this limitation, a suspension culture method to reverse EEO polarity was developed based on methods reported for human enteroid and airway organoids (Co et al, 2019, Co et al, 2021, Kakni et al, 2023, Wijesekara et al, 2023. Our studies demonstrate that this culture method alters the polarity of EEO without compromising their physiological hormone response and viability.…”
Section: Introductionmentioning
confidence: 98%
“…A defining feature of BME-embedded three-dimensional organoid structures is a polarized epithelium with a central lumen. The apical-in/basal-out polarity of EEO presents a challenge to study epithelial interactions with embryos or infection by microbes or viruses that reside in the uterine lumen (Boretto et al, 2019, Boretto et al, 2017, Co et al, 2019, Simintiras et al, 2021, Kakni et al, 2023, Wijesekara et al, 2023. To overcome this limitation, a suspension culture method to reverse EEO polarity was developed based on methods reported for human enteroid and airway organoids (Co et al, 2019, Co et al, 2021, Kakni et al, 2023, Wijesekara et al, 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exclusion of the mucus barrier, villi topography, and fluidic forces can distort fundamental assumptions about nanocarrier-tissue interactions, leading to inaccurate assessments of drug bioavailability. Strategies to overcome these limitations comprise the integration of mucus producing cell types, induced pluripotent stem cells or patient-derived material, and their cultivation in microfluidic chips, resulting in the formation of complex threedimensional micro-tissues [30][31][32][33][34][35] . While these approaches offer the potential to create test systems with improved physiological relevance, they require a high level of expertise in the fields of cell biology as well as engineering and are currently limited by high production costs and low throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Apical‐out organoids were first published by Co et al, who have demonstrated that human intestinal organoids that usually grow embedded in a three‐dimensional extracellular matrix (ECM) can reverse their polarity when they are cultured in a floating manner in medium without ECM 12 . This method has now been adopted by many other labs and expanded to different animal species, for example, pigs, 13 chickens, 14 cows 15 and dogs, 16 and also organoids derived from human iPSCs and embryonic stem cells 17,18 . Remarkably, regardless of the species from which the organoids were derived, the majority of these studies utilised their apical‐out organoids within the initial 7 days following the induction of polarity reversal 13,16,17,19–21 .…”
Section: Introductionmentioning
confidence: 99%